Front Cover: Revisiting Bond Breaking and Making in EuCo2P2: Where are the Electrons? (Chem. Eur. J. 23/2019). Issue 23 (19th March 2019) - Yannello, Vincent; Guillou, Francois; Yaroslavtsev, Alexander A.; Tener, Zachary P.; Wilhelm, Fabrice; Yaresko, Alexander N.; Molodtsov, Serguei L.; Scherz, Andreas; Rogalev, Andrei; Shatruk, Michael
Abstract : Pressure‐induced structural collapse in EuCo2 P2 causes electron density redistribution, which defies commonly used formal oxidation states. The phase‐transition behavior has been elucidated by a combination of X‐ray absorption spectroscopy and band structure calculations, which demonstrate that the changes in the electronic structure of metallic systems with strongly hybridized states can be contradictory to the effects expected from the formal electron counting schemes. More information can be found in the Communication by A. Rogalev, M. Shatruk, et al. onpage 5865 .